Plasma-free metal-assisted chemical etching producing three-dimensional gallium nitride structures - Liao, Yikai (2024)
Gallium nitride (GaN) is a third-generation wide bandgap semiconductor well-suited for power electronics and ultraviolet optoelectronics. Traditional plasma-based dry etching is widely used for producing three-dimensional (3D) GaN structures, nevertheless resulting in plasma-induced surface damage, which is unfavorable for device performance. This paper seeks to provide a plasma-free metal-assisted chemical etching (MacEtch) method as an alternative to the traditional dry etching method to fabricate 3D GaN structures. As a novel wet etching method, MacEtch is able to produce various GaN structures with dimensions from several to hundreds of micrometers with a nearly vertical sidewall profile. The formation process and mechanism of the GaN structures, and the influence of the etchant components are carefully studied. By means of potassium hydroxide post-treatment, GaN structures with vertical and smooth sidewalls are produced. MacEtch of GaN in this work has demonstrated simplicity and versatility for fabricating a wide range of 3D GaN structures with the etching mechanism fully elucidated.